1998
DOI: 10.1111/j.1559-1816.1998.tb01660.x
|View full text |Cite
|
Sign up to set email alerts
|

An Attributional Perspective on African American Adults' Exercise Behavior1

Abstract: The present study examined attributional patterns for successful and unsuccessful exercise behavior change in a sample of African American adults. Subjects typically reported the primary causes of successful exercise change to be of a motivational and personal nature, whereas attributions for unsuccessful change were primarily concerned with time management. Multivariate analyses indicated successes being attributed to internal, stable, and personally controllable causes, and failures to internal, unstable, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…These strategies have each been linked individually to physical activity (eg, [17][18][19]. For the purpose of this study, 3 self-regulation strategies from Zimmerman's 15 model were selected for examination.…”
mentioning
confidence: 99%
“…These strategies have each been linked individually to physical activity (eg, [17][18][19]. For the purpose of this study, 3 self-regulation strategies from Zimmerman's 15 model were selected for examination.…”
mentioning
confidence: 99%
“…Personal control refers to the ability of the person to control the primary cause (controllable or uncontrollable), while external control refers to the ability of others to control the primary cause (controllable or uncontrollable). The external control dimension has been excluded from previous research on attributions for PA and may not be useful here as these types of attributions cannot be self-regulated (Minifee & McAuley, 1998;Nickel & Spink, 2010). Therefore, the external control dimension was measured, but there are no hypothesized results for this dimension.…”
Section: Attributions the Attributions Measurement Used Was The Causmentioning
confidence: 99%
“…More internal, stable, and personally controllable attributions (e.g., long term effort) lead to higher frequency and higher perceived success of PA (Minifee & McAuley, 1998;Nickel & Spink, 2010). Individuals with a lower frequency of PA behavior and individuals who failed to adhere to an exercise program make less internal, more unstable, and more personally uncontrollable attributions (Minifee & McAuley, 1998). McAuley, Poag, Gleason, and Wraith (1990) also found that individuals who dropped out of structured exercise programs reported more unstable causal attributions.…”
Section: Attribution Theorymentioning
confidence: 99%
“…Research applying attribution theory to physical activity outcomes has typically found that those who perceive themselves as successful tend to report higher levels of internality, controllability, and stability than do those who perceive themselves as failing (Courneya & McAuley, 1993, 1996; McAuley, 1991; Minifee & McAuley, 1998; Shields, Brawley, & Lindover, 2005). For the most part, these studies have involved the examination of attributions associated with activity outcomes, such as attendance in an exercise class (Courneya & McAuley, 1996; Shields et al., 2005) or simple physical activity change outcomes (Minifee & McAuley, 1998). However, most have not considered success in terms of being active enough to achieve health benefits as an outcome.…”
mentioning
confidence: 99%
“…Weiner (1985, 1986) postulated that outcomes attributed to stable causes will be expected to be repeated in the future with a greater degree of certainty than outcomes attributed to unstable causes. In terms of addressing this principle, findings from activity settings have been mixed when future expectancies have been operationalized as expected success, with studies finding support (Minifee & McAuley, 1998), partial support (Schoeneman & Curry, 1990), or no support (Courneya & McAuley, 1996) for the proposed interaction between perceived outcome and the casual dimension of stability. As Weiner (1985, 1986) mentioned a number of constructs pertaining to future expectancies, the intent in the present study is to examine the relationship between stability and expectancy using one that has not yet been examined with regard to physical activity for health benefits; that is, certainty of similar future outcomes.…”
mentioning
confidence: 99%